Determinants of attitude toward proposed good and services tax among business communities in Malaysia - Bidin, Zainol; Marimuthu, Munusamy; Derashid, Chek; Md. Idris, Kamil; Ahmad, Norsiah (2016)
Goods and Services Tax (GST) is an indirect tax reform.The decision to implement GST was made on 1 April 2015.The Malaysian business communities are concerned that Goods and Service Tax (GST) would affect their business.In order to comply with the new system, GST, Malaysian citizen need to have a positive attitude toward the GST. The rational is that taxpayers need to be positive in attitude for voluntarily compliance.By determining what factors could possibly influence attitude towards GST by business community and consequently could improve the compliance rate indirectly.Thus, this study is attempts to identify the determinants of attitude towards the proposed GST implementation in Malaysia. A total of 521 usable questionnaires from business community in 2014 were analyzed using multiple regressions.The results revealed and supported that awareness; understanding, and preparedness were significantly in influencing the attitude towards proposed GST implementation in Malaysia among the business communities. Suggestions to the tax authority and limitation of the study were also discussed.